A Study of EFL Students’ Perspective on Ambiguity Tolerance - Fera Aldila Kurniasari; Lilia Indriani (English Learning Innovation (englie), 2021)
This research aims to investigate the EFL students' perspective on ambiguity tolerance. The researcher used a descriptive qualitative approach for this research. To collect the data, the researcher used the Second Language Tolerance of Ambiguity Scale (SLTAS) as the instrument. This research involved 30 students of the 5th semester of Tidar University Magelang as the participant. The result shows that the participants have low ambiguity tolerance in the term reading and listening and more tolerance in speaking and writing.